1996
DOI: 10.1295/polymj.28.507
|View full text |Cite
|
Sign up to set email alerts
|

Morphological Formation of the Regenerated Cellulose Membranes Recovered from Its Cuprammonium Solution Using Various Coagulants

Abstract: ABSTRACT:Morphological formation of the regenerated cellulose membranes from its cuprammonium hydroxide solution was investigated in connection with the change in the complex form between cellulose and cuprammonium hydroxide and material transportation during coagulation process using various aqueous coagulants (H +, Na +, K +, NH4 +, Ca 2 +, Mg 2 + with various counter ions). Scanning electron microscopically observation revealed that the morphological distribution estimated by pore size distribution in the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
20
0
1

Year Published

1997
1997
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 9 publications
(10 reference statements)
2
20
0
1
Order By: Relevance
“…It is known that the membrane structure formed by alkaline coagulation in the cuprammonium rayon method is a dense structure. 29 Our result of cuprammonium membrane is in good agreement with this report. On the basis of these results, we conclude that the NMMO and cuprammonium membranes prepared from the casting solution with 8 wt % cellulose had the same structure and could be categorized as nonporous membranes.…”
Section: Membrane Morphologysupporting
confidence: 92%
“…It is known that the membrane structure formed by alkaline coagulation in the cuprammonium rayon method is a dense structure. 29 Our result of cuprammonium membrane is in good agreement with this report. On the basis of these results, we conclude that the NMMO and cuprammonium membranes prepared from the casting solution with 8 wt % cellulose had the same structure and could be categorized as nonporous membranes.…”
Section: Membrane Morphologysupporting
confidence: 92%
“…11 • 12 Of the coagulants used, aq sulfuric acid was proved to decompose promptly the original cellulose jcuprammonium hydroxide complex, giving very porous structure, and in contrast, aq sodium hydroxide gives a gel with definite complex form, leading to very dense structure. 10 Further, we found that morphology and amorphous structure of the regenerated cellulose membranes dramatically changed as functions of both concentration of coagulant and polymer concentration when aq sulfuric acid was used as coagulant. 13 It is therefore interesting to examine if the above phenomenological observation for the cellulose membranes is also applicable to the cellulose blend membranes.…”
mentioning
confidence: 81%
“…In another line of studies Okajima and his coworkers have already studied on the dissolved state (C 2 , C 3 -coordinate 15 chelate form) of cellulose in cuprammonium hydroxide, 9 the morphology of the regenerated cellulose membranes recovered from its cuprammonium hydroxide solution in relation to the changes in circular dichroism (CD) spectra of the cellulose solution during its coagulation process, 10 and the dimensional stability and morphology of the membranes obtained by changing coagulants in view of amorphous parameters. 11 • 12 Of the coagulants used, aq sulfuric acid was proved to decompose promptly the original cellulose jcuprammonium hydroxide complex, giving very porous structure, and in contrast, aq sodium hydroxide gives a gel with definite complex form, leading to very dense structure.…”
mentioning
confidence: 99%
“…Pada kasus tersebut kecepatan adukan tidak menghasilkan ukuran-ukuran partikel yang lebih kecil karena tidak cukup kuat untuk memecahkan koagulasi yang terjadi. Hal lain yang terjadi adalah proses koagulasi yang terjadi sangat cepat dikarenakan konsentrasi larutan garam yang tinggi [18,19]. Terlihat larutan selulosa yang dimasukkan langsung mengeras ketika menyentuh larutan garam.…”
Section: D) Proses Koagulasi Pada Larutan Garamunclassified